Earthfill Dams Response to Earthquake Excitation -Khassa Chai Dam as a Case Study - Fattah, Mohammed Y.; Alwash, Haider H.; Hadi, Sarah A. (Al-Nahrain Journal for Engineering Sciences, 2017)
In this paper, a dynamic analysis has been carried out on zoned earthdam subjected to earthquake excitation in which pore water pressure, effective stresses and displacements are calculated. The finite element method is used and the computer program Geo-Studio is adopted in the analysis through its sub-programs SEEP/W and QUAKE/W. A case study is considered to be Khassa Chai dam which is located on Khassa Chai river north of Iraq and consists of zoned embankment with a total length of 3.34 km. The selected earthquake for the analysis is El-Centro earthquake with a period of 10 sec and different amplitudes of acceleration. The time of the analysis is taken as 600 sec. with a time step (?t = 0.05 sec.) to investigate the behavior of the soil for a period of time after the earthquake has stopped, a free vibration period is included in the analysis. It was concluded that the value of pore water pressure generated at the base of the core is greater than that in the upper parts of dam. The horizontal and vertical effective stresses continue to decrease during the period of analysis 600 sec. which indicates that the soil continues to weaken during this period, the horizontal displacement increases with depth of the point from the crest and the largest horizontal displacement will be at the base of the dam at time 60 sec and There is attenuation of the acceleration to some degree depending on the amplitude of the input horizontal acceleration. The maximum horizontal displacement decreases by about 37%, 45% and 49% when using a horizontal drain 2 m thick at the downstream under a peak acceleration of 0.05g, 0.1g and 0.2g, respectively.